Correlation of Echoradiography Pulmonary to Left Atrial Ratio (ePLAR) with Right Heart Catheterization Parameters in Pulmonal Arterial Hypertension. (25th January 2023) - Fernando, H; Yanni, M; Hariyanto, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Until now, right heart catheterization is still the gold standard for pulmonary hypertension examination, but this examination is invasive, has a risk of action, and is limited. Echocardiography provides an alternative examination that is easier, safer, cheaper, and more effective in evaluating pulmonary hypertension. Various echocardiographic parameters have been used to assess pulmonary hypertension but no parameter can distinguish the hemodynamics of pulmonary hypertension. Echocardiography pulmonary to left atrial ratio (ePLAR) is a new echocardiographic parameter that is formulated by the maximal tricuspid regurgitation velocity (TR Vmax) divided by the mitral E/e'. This simple parameter can determine precapillary pulmonary hypertension Purpose: The aim of this study is to determine the correlation of ePLAR with right heart catheterization parameters in pulmonary arterial hypertension patients. Methods: This is a cross-sectional study in the pulmonary arterial hypertension group conducted at M. Djamil Hospital from August 2021 to May 2022. Respondents underwent an echocardiography and right heart catheterization prosedure. The correlation of ePLAR with right heart catheterization parameters was assessed using the Spearman correlation test. Result: The research subjects were 32 patients with pulmonary arterial hypertension, 20 women and 12 men, the median age was 21.50 (8-54) years and the most common cause of pulmonary arterial hypertension was congenital heart disease. The median value of ePLAR was 0.44(0.30-0.77) m/s, while the mean value of mPAP was 54.40 ± 16.24 mmHg and the median value of PVR was 8.39 (3.21-29.50) WU. Based on the Spearman correlation test, it was found that the ePLAR had a moderate positive correlation (r=0.554) with the mPAP and was statistically significant (p=0.001). The ePLAR had a strong positive correlation (r=0.779) with the PVR and was statistically significant (p<0.001) Conclusion: There was a moderate and significant positive correlation between ePLAR and mPAP, there was a strong and significant positive correlation between ePLAR and PVR in patients with pulmonary arterial hypertension. Correlation ePLAR with mPAP Correlation ePLAR with PVR